Analysis Of Liquidity, Solvency, And Profitability Ratios In Measuring Financial Performance At PT. Bukit Asam Tbk Indonesia - Mhd. Ridho Ermansyah Lubis; Tia Aryani Sitanggang; Devi Mayasari; Della Puspita; Nina Andriany Nasution (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to describe and analyze the financial performance of PT Bukit Asam Tbk Indonesia, which is reviewed using the analysis of liquidity, solvency, and profitability ratios. The analysis method used is the descriptive analysis method. The data used in this study is secondary data derived from the main website of PT Bukit Asam Tbk and focuses on the financial statements for the period 2018–2022. The results of the research analysis show that the company performance of PT Bukit Asam Tbk Indonesia in terms of liquidity, solvency, and profitability ratios is in the